Defibrillation testing of subcutaneous versus transvenous defibrillators in the clinical practice: a nationwide survey in Italy. (14th October 2021) - Migliore, F; Viani, S; Ziacchi, M; Ottaviano, L; Checchi, L; Francia, P; D'Onofrio, A; Bisignani, G; Dello Russo, A; De Filippo, P; Solimene, F; Pisano, E; et al.
Abstract: Aims: According to current guidelines, defibrillation testing (DT) for efficacy can be omitted in patients undergoing transvenous implantable cardioverter–defibrillator (T-ICD) implantation. DT is still recommended for patients at risk for a high defibrillation threshold (e.g. hypertrophic cardiomyopathy, arrhythmogenic right ventricular cardiomyopathy, right-sided implantations) and for ICD generator changes. Moreover, a class I recommendation remains to perform DT during the implantation of subcutaneous ICD (S-ICD). The aim of the present survey was to analyze the current practice of DT during T-ICD and S-ICD implantations in Italy. Methods: In March 2021, an ad hoc questionnaire on the current performance of DT and the standard practice adopted during testing was completed by 72 operators at Italian centers implanting S-ICD and T-ICD. Results: 48 (67%) operators reported never performing DT during de-novo T-ICD implantations, while no operators perform it systematically. The remaining respondents perform it in specific cases: right sided implantations (54%), poor signal sensing (46%), secondary prevention patients (42%), arrhythmic syndromes (13%), hypertrophic cardiomyopathy (8%). DT is never performed at T-ICD generator change. At the time of de-novo S-ICD implantation, DT is never performed by 9 (13%) operators and performed systematically by 48 (66%). The remaining operators perform DT in cases of: secondary prevention patients (73%), sub-optimal S-ICD placement (33%), non-compromised ejection fraction (33%) or obese patients (7%). DT is not performed at S-ICD generator change by 92% of operators. DT is conducted by delivering a first shock energy of 65J by 60% of operators, while the remaining 40% test lower energy values. The most frequently reported conditions for revising the system at the end of de- novo implantation procedure is high shock impedance (54%) and sub-optimal S-ICD placement or high PRAETORIAN score (50%). With adequately low shock impedance and optimal system placement, 37% of operators would accept a defibrillation margin <15J. Conclusion: In current clinical practice, the vast majority of operators omit DT at T-ICD implantation, even when still recommended in the guidelines. DT is also frequently omitted at S-ICD implantation. We also report a wide variability among operators in the procedures followed during DT and in the criteria applied for defining the procedural success. Funding Acknowledgement: Type of funding sources: None.